2016
DOI: 10.12775/ths.2015.002
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice toward outgroups as a Strategy to Deal with Mortality Threat: Simple Reaction with a Complex Foundation

Abstract: Abstract. Prejudice and stereotypes are two negative phenomena influencing our everyday lives. Current theory proposes that they are the effects of death cues acting mainly subconsciously, causing a potential for anxiety and provoking to defend our beliefs and maintain self-esteem. Although numerous studies have confirmed the relation between mortality salience and negative attitudes toward outgroups, moderators of this relation drew less attention so far. The following paper proposes three factors to consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A series of studies have demonstrated that threats to the self either via reminder of mortality (Burke, Martens, & Faucher, 2010;Maj & Kossowska, 2015) or through negative feedback about oneself (Allen & Sherman, 2011;Fein & Spencer, 1997;Spencer, Fein, Wolfe, Fong, & Duinn, 1998) can lead participants to increase their reliance on negative stereotypes about others. Allen and Sherman demonstrated that this effect was due to a greater focus on the negative attributes of out-groups, suggesting that Soc Just Res (2017) 30:323-354 331 these effects do represent a means of self-protection through the devaluation of nonself groups.…”
Section: Prejudice and The Conceptual Selfmentioning
confidence: 99%
“…A series of studies have demonstrated that threats to the self either via reminder of mortality (Burke, Martens, & Faucher, 2010;Maj & Kossowska, 2015) or through negative feedback about oneself (Allen & Sherman, 2011;Fein & Spencer, 1997;Spencer, Fein, Wolfe, Fong, & Duinn, 1998) can lead participants to increase their reliance on negative stereotypes about others. Allen and Sherman demonstrated that this effect was due to a greater focus on the negative attributes of out-groups, suggesting that Soc Just Res (2017) 30:323-354 331 these effects do represent a means of self-protection through the devaluation of nonself groups.…”
Section: Prejudice and The Conceptual Selfmentioning
confidence: 99%
“…Both -queer theory and social psychology's terror management theory (Greenberg et al, 1986) -assume death attitudes to precede gender stereotypes. If death attitudes precede gender stereotypes and other kinds of social prejudice (Maj and Kossowska, 2016;Wong, 2008), then they promise for a more radical , intersectional approach to psychosocial intervention. However, Butler (1990Butler ( , 1997 explains the development of gender stereotypes with outdated Freudian psychoanalysis.…”
Section: Objectivementioning
confidence: 99%
“…Wong (2008) explains that negative death valence precedes death denial and positive death valence precedes death acceptance. If death acceptance reduces social prejudice (Maj and Kossowska, 2016;Wong, 2008), for example based on gender, then it could serve as a framework for a more radical and a possibly more intersectional approach to psychosocial intervention. So far, terror management research on gender stereotypes did not account for death acceptance, nor did it differentiate between sex and gender.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation